2002
DOI: 10.1046/j.0953-816x.2001.01856.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain catecholamine metabolism in catechol‐O‐methyltransferase (COMT)‐deficient mice

Abstract: Catechol-O-methyltransferase (COMT) catalyses the O-methylation of compounds having a catechol structure and its main function involves the elimination of biologically active or toxic catechols and their metabolites. By means of homologous recombination in embryonic stem cells, a strain of mice has been produced in which the gene encoding the COMT enzyme is disrupted. We report here the levels of catecholamines and their metabolites in striatal extracellular fluid in these mice as well as in homogenates from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
142
3
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 31 publications
13
142
3
2
Order By: Relevance
“…Furthermore, several studies have found associations of val158met and panic disorder specific to women (Domschke et al, 2004;Woo et al, 2004). These results also fit well with the fact that most anxiety (and depressive) disorders are more common in women, and are consistent with preclinical data indicating the possibility for sexually dimorphic effects of COMT variants on catecholamine metabolism (Huotari et al, 2002). This observation must be interpreted with caution, however, because there were more than twice as many women as men in our sample, so we might have lacked power to detect a signal in men.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, several studies have found associations of val158met and panic disorder specific to women (Domschke et al, 2004;Woo et al, 2004). These results also fit well with the fact that most anxiety (and depressive) disorders are more common in women, and are consistent with preclinical data indicating the possibility for sexually dimorphic effects of COMT variants on catecholamine metabolism (Huotari et al, 2002). This observation must be interpreted with caution, however, because there were more than twice as many women as men in our sample, so we might have lacked power to detect a signal in men.…”
Section: Discussionsupporting
confidence: 85%
“…However, animal studies indicate that COMT plays only a minimal role in the clearance of synaptic dopamine, even under conditions of low dopamine transporter activity. [45][46][47] Furthermore, COMT genotype appears to account for only a small amount (2-4%) of shared variance with WCST performance. 52,105 Thus, this small effect of COMT genotype on cognitive performance may be especially difficult to detect in younger and more heterogeneous sample of schizophrenia patients.…”
Section: Discussionmentioning
confidence: 96%
“…29,[39][40][41][42][43] Elimination of extracellular dopamine relies on synaptic reuptake (via dopamine transporter and norepinephrine transporter) as well degradation by monoamine oxidase and catechol-O-methyl transferase (COMT). [44][45][46][47] Owing to its role in the catabolism of dopamine, the COMT gene has been extensively studied as a schizophrenia candidate gene. In humans, there is a common V 158 M functional polymorphism 48 where a methionine (Met) substituted for a valine (Val) leads to a four-fold reduction in COMT enzyme activity.…”
mentioning
confidence: 99%
“…Previous experimental data indicate that COMT is especially relevant in modulating prefrontal cortical dopamine neurotransmission. First, studies of COMT knockout mice have demonstrated that dopamine levels are increased in the prefrontal cortex of these mice under varying conditions, but not in the striatum (Gogos et al, 1998;Huotari et al, 2002). Pharmacological studies in rats have also shown that the catabolic flux of synaptic dopamine through the COMT pathway is much greater in the prefrontal cortex as compared to the striatum (Karoum et al, 1994).…”
Section: Introductionmentioning
confidence: 99%